2017
DOI: 10.1038/s41598-017-01701-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Purcell effect reveals obliquely ordered phosphorescent emitters in Organic LEDs

Abstract: The non-isotropic alignment of molecules can increase the interaction efficiency with propagating light fields. This applies to both emissive and absorptive systems and can be exploited for achieving unprecedented efficiencies of organic opto-electronic devices such as organic light-emitting diodes. Optical analysis has revealed certain phosphorescent emitters to align spontaneously in an advantageous orientation. Unfortunately, established approaches only determine an average orientation because emission patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…For these molecules, the observed isotropy can either be due to random orientation of the molecule or may be indicative of a situation where molecules are aligned on the substrate but have their transition dipole moments slanted such that they contribute equally in all three emission directions. [6,11] Very recently, X-ray diffraction studies have shown that phosphorescent platinum emitters can form large crystals with a nearly perfect horizontal alignment of the transition dipoles. [12] In contrast, the light-emitting structures that are traditionally used in OLEDs are generally believed to comprise of amorphous films which are generally not amenable to investigation by X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…For these molecules, the observed isotropy can either be due to random orientation of the molecule or may be indicative of a situation where molecules are aligned on the substrate but have their transition dipole moments slanted such that they contribute equally in all three emission directions. [6,11] Very recently, X-ray diffraction studies have shown that phosphorescent platinum emitters can form large crystals with a nearly perfect horizontal alignment of the transition dipoles. [12] In contrast, the light-emitting structures that are traditionally used in OLEDs are generally believed to comprise of amorphous films which are generally not amenable to investigation by X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…s-polarization emission spectra of 10° to 70° emission angles are shown in (a,b), unpolarized spectra for 0° emission angle in (c,d), and spolarization when using a cylindrical lens in (e,f). For non-0° angles, p-polarized light must be filtered as it contains emitter orientation effects [21]. The OLED stack and the optical emission paths are shown in (h), upper half: polarizer and no lens, centre: no additional optics, lower half: with polarizer and cylindrical lens (higher angle modes trapped in the substrate without a lens are outcoupled here).…”
Section: Figure 2 Comparison Of Simulated Emission Spectra With and Without Cylindrical Lens For Different Emission Zonesmentioning
confidence: 99%
“…The simulation relies on the dyadic Green's function approach [17] implemented for OLED modelling in the tool RadiatingSlabs as reported previously [4,7,9,15,16,18]. This numerical model includes arbitrary orientation distributions, Purcell effect consideration as well as multiple incoherent reflexes in the substrates of large area sources.…”
Section: Simulation and Data Analysismentioning
confidence: 99%
“…Such approach requires the precise knowledge of the stack geometry as well as that of the material properties. Advanced approaches suggested a very good alignment of the emitting ensembles recently [9,10]. Regarding emitter orientation, especially the anisotropic properties of both the thin film system as well as that of the emitting layer (EML) need to be considered.…”
Section: Introductionmentioning
confidence: 99%